2020
DOI: 10.1109/access.2020.3017634
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Capacity of Massive MIMO With 1-Bit ADCs and 1-Bit DACs at the Receiver and at the Transmitter

Abstract: In this paper, we investigate the capacity of massive multiple-input multiple-output (MIMO) systems corrupted by complex-valued additive white Gaussian noise (AWGN) when both the transmitter and the receiver employ 1-bit digital-to-analog converters (DACs) and 1-bit analog-to-digital-converters (ADCs). As a result of 1-bit DACs and ADCs, the transmitted and received symbols, as well as the transmit-and receive-side noisy channel state information (CSI) are assumed to be quantized to 1-bit of information. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Note that, when K < N (i.e., when the number of data streams is strictly smaller than the number of transmit antennas, which is generally the case in downlink massive MIMO systems), C x in ( 8) is rank-deficient and G TX cannot be computed as in (11); 2 nonetheless, it can still be obtained via (13), which does not involve the inversion of C x . Furthermore, C t in ( 9) can be computed in closed form as in ( 14) at the top of the page [5].…”
Section: A Linearization At the Transmittermentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, when K < N (i.e., when the number of data streams is strictly smaller than the number of transmit antennas, which is generally the case in downlink massive MIMO systems), C x in ( 8) is rank-deficient and G TX cannot be computed as in (11); 2 nonetheless, it can still be obtained via (13), which does not involve the inversion of C x . Furthermore, C t in ( 9) can be computed in closed form as in ( 14) at the top of the page [5].…”
Section: A Linearization At the Transmittermentioning
confidence: 99%
“…For instance, [10] studied the 1-bit multiple-input single-output capacity with perfect channel state information (CSI) at both the transmitter and receiver. Moreover, [11] described the 1-bit MIMO capacity with imperfect CSI assuming that the number of transmit or receive antennas tends to infinity. Lastly, [12] showed that a proper combination of transmit beamforming and equiprobable signaling allows the system to operate close to the 1-bit MIMO capacity.…”
Section: Introductionmentioning
confidence: 99%
“…where P ∩ (i, j) is given by (59). The bounds specified by ( 57)-( 59) are readily computable even for very large numbers of antennas.…”
Section: E Tr (Diag(hhmentioning
confidence: 99%
“…Most importantly, because the entries of h are IID, the position of those −1 values is immaterial and only their totals i and j matter. Altogether, the joint distribution of ℜ{a k }, ℑ{a k }, ℜ{a 1 } and ℑ{a 1 } is as in (93) and, plugging it in (88) and tediously integrating over two of the dimensions, what emerges is (59) with the dependence on i and j made explicit and with erfc(•) the complementary error function.…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation